2024
DOI: 10.1002/anie.202318523
|View full text |Cite
|
Sign up to set email alerts
|

The Retaining Pse5Ac7Ac Pseudaminyltransferase KpsS1 Defines a Previously Unreported glycosyltransferase family (GT118)

Abigail J. Walklett,
Emily K. P. Flack,
Harriet S. Chidwick
et al.

Abstract: Cell surface sugar 5,7‐diacetyl pseudaminic acid (Pse5Ac7Ac) is a bacterial analogue of the ubiquitous sialic acid, Neu5Ac, and contributes to the virulence of a number of multidrug resistant bacteria, including ESKAPE pathogens Pseudomonas aeruginosa, and Acinetobacter baumannii. Despite its discovery in the surface glycans of bacteria over thirty years ago, to date no glycosyltransferase enzymes (GTs) dedicated to the synthesis of a pseudaminic acid glycosidic linkage have been unequivocally characterised in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…During the course of our study, a report showed that KpsS1 was able to glycosylate Pse in an in vitro enzymatic reaction. [5] Our study, however, provides directed evidence of the in vivo role of this enzyme in A. baumannii, which complements very well with the recent report.…”
Section: Introductionsupporting
confidence: 91%
“…During the course of our study, a report showed that KpsS1 was able to glycosylate Pse in an in vitro enzymatic reaction. [5] Our study, however, provides directed evidence of the in vivo role of this enzyme in A. baumannii, which complements very well with the recent report.…”
Section: Introductionsupporting
confidence: 91%